Agrarian Conflict Resolution, Forestry Companies Versus Plantation Companies in North Kalimantan - Brata, Nugroho Trisnu; Setyowati, Dewi Liesnoor; Setiaji, Khasan (Komunitas, 2022)
Agrarian conflict often occurs when two or more concerned parties have different interests in the same land. This study aims to analyzing the conflict between PT. NJL and PT. Adindo. The research employed qualitative method, the location in Sei Menggaris, Nunukan, North Kalimantan was carried out in August 2020. The results showed that the status of area, which has the permit of Cultivation Right owned by PT. NJL for an area of 17,000 hectares, there is an area of 3,510 hectares for Industrial Plantation Forest overlaps with the Business Permit that has already been owned by PT. Adindo which is engaged in the industrial plantation forest. As conclusion, a resolution that did not harm all parties, including workers. An agreement was reached that an area of approximately 2,800 ha which was not the object of the conflict and had been cultivated into oil palm plantations by PT. NJL would be continued so that local people would not lose their jobs.